Composite, method for producing molded article, and molded article
Patent Information
- Application Number
- JP2021041091
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-15
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2041-03-15
Smart Images

Figure 0007651891000003 
Figure 0007651891000004 
Figure 0007651891000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite, a method for producing a molded article, and a molded article. [Background technology]
[0002] It has been practiced for a long time to deposit fibrous materials and obtain a sheet- or film-like molded product by applying a bonding force between the deposited fibers. A typical example is the production of paper by papermaking using water. Paper produced by papermaking generally has a structure in which, for example, cellulose fibers derived from wood or the like are entangled with each other and partially bound to each other by a binder.
[0003] However, because the papermaking method is a wet method, it is necessary to use a large amount of water, and after the paper is formed, it is necessary to dehydrate and dry it, which requires a lot of energy and time. In addition, the water used must be properly treated as wastewater. Therefore, it is becoming difficult to meet the recent demands for energy conservation and environmental protection. In addition, the equipment used in the papermaking method often requires large utilities such as water, electricity, and drainage equipment, and it is difficult to miniaturize it. From these points of view, a method called a dry method that does not use any water or almost no water is expected to replace the papermaking method.
[0004] One known dry process involves using a binder together with the fibers to improve the strength of the resulting paper, depositing a mixture of the fibers and the binder to form a web, and then pressurizing and heating the web to form a sheet (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2018 / 043034 Summary of the Invention [Problem to be solved by the invention]
[0006] However, simply heating and pressurizing a mixture of fibers and resin as described above may result in insufficient wetting and spreading of the resin, resulting in a small bonding area between the fibers, and making it difficult to ensure sufficient strength for the sheet as a molded body. [Means for solving the problem]
[0007] The present invention has been made to solve the above-mentioned problems, and can be realized as the following application examples.
[0008] The composite according to the application example of the present invention includes thermoplastic particles made of a thermoplastic material, and inorganic particles surface-treated with at least one surface treatment agent selected from the group consisting of a fluorine-containing compound and a silicon-containing compound; The inorganic particles include composite particles attached to the surfaces of the thermoplastic particles.
[0009] In addition, a method for producing a molded body according to another application example of the present invention includes a depositing step of depositing a mixture containing fibers and the composite according to the application example of the present invention; and a heating and pressurizing step of heating and pressurizing the mixture.
[0010] In addition, a molded article according to another application example of the present invention includes fibers and Inorganic particles that have been surface-treated with at least one surface treatment agent selected from the group consisting of fluorine-containing compounds and silicon-containing compounds; and a thermoplastic material that bonds the fibers and the inorganic particles. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic diagram showing a composite according to a preferred embodiment of the present invention. [Diagram 2]FIG. 2 is a schematic side view showing the configuration of a molding manufacturing apparatus according to a preferred embodiment. [Diagram 3] FIG. 3 is a diagram showing the steps executed by the molding manufacturing apparatus shown in FIG. 2 in order. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Preferred embodiments of the present invention will now be described in detail. [1] Complex First, the complex of the present invention will be described. FIG. 1 is a schematic diagram showing a composite according to a preferred embodiment of the present invention.
[0013] The composite C10 of the present invention includes thermoplastic particles C2 made of a thermoplastic material and inorganic particles C3 surface-treated with at least one surface treatment agent selected from the group consisting of fluorine-containing compounds and silicon-containing compounds. The composite C1 includes the inorganic particles C3 attached to the surfaces of the thermoplastic particles C2. In other words, at least a portion of the inorganic particles C3 included in the composite C10 is attached to the surfaces of the thermoplastic particles C2.
[0014] This makes it possible to provide a composite C10 that can be suitably used for producing a molded body that contains fibers and has excellent strength. In addition, a molded body having a desired shape can be suitably produced even with almost no water. That is, it can be suitably applied to a dry molding method. Therefore, it is advantageous from the viewpoints of productivity and production cost of the molded body, energy saving, and miniaturization of the manufacturing equipment for the molded body. In this specification, the dry molding method refers to a method in which the molding raw material is not immersed in a liquid containing water in the process of producing a molded body, and a method using a small amount of water, for example, a method in which a liquid containing water is sprayed on the molding raw material, etc., is also included in the dry molding method.
[0015] Such excellent effects are believed to be due to the following reasons. That is, by including inorganic particles C3 having the above-mentioned surface treatment on the surface of thermoplastic particles C2, the surface free energy can be reduced compared to the case where thermoplastic particles are used alone, that is, where thermoplastic particles to which inorganic particles are not attached are used, or where inorganic particles to which no surface treatment is applied are attached to the surface of thermoplastic particles. As a result, when heated during the production of a molded product using the fibers, the composite C10 is easily wetted and spread on the surface of the fibers. As a result, the adhesion between the fibers and the thermoplastic material is excellent in the molded product finally obtained, and the strength of the molded product can be excellent.
[0016] In addition, by using the inorganic particles C3 that have been surface-treated with the above-mentioned surface treatment agent, aggregation of the thermoplastic particles C2 and the composite particles C1 is suitably prevented. In addition, by including the inorganic particles C3 that have been surface-treated with the above-mentioned surface treatment agent, the fluidity and ease of handling of the composite C10 are improved. This makes it possible to particularly improve the productivity of the molded body.
[0017] [1-1] Composite particles Composite C10 includes composite particles C1 having inorganic particles C3 attached to the surfaces of thermoplastic particles C2.
[0018] The composite particle C1 contained in the composite C10 may be a single inorganic particle C3 attached to the surface of a single thermoplastic particle C2, but it is preferable that the composite particle C1 is a particle having a single thermoplastic particle C2 and multiple inorganic particles C3 attached to the surface of the single thermoplastic particle C2. This allows the above-mentioned effects of the present invention to be more pronounced.
[0019] The average particle size of the composite particles C1 is preferably 1.0 μm or more and 100 μm or less, more preferably 2.0 μm or more and 70 μm or less, and even more preferably 3.0 μm or more and 50 μm or less. This allows the above-mentioned effects of the present invention to be more pronounced.
[0020] In this specification, the average particle size refers to the average particle size on a volume basis unless otherwise specified. The average particle size can be determined, for example, by measurement using Nanotrac UPA (manufactured by Nikkiso Co., Ltd.).
[0021] [1-1-1]Thermoplastic particles The thermoplastic particles C2 are made of a thermoplastic material. Examples of the thermoplastic material constituting the thermoplastic particles C2 include various thermoplastic resins such as polystyrene, acrylonitrile-styrene copolymer, acrylonitrile-butadiene-styrene copolymer, etc., acrylic resin, styrene-acrylic copolymer resin, olefin resin, vinyl chloride resin, polyester resin, polyamide resin, polyurethane resin, polyvinyl alcohol resin, etc., thermoplastic starch, etc., and one or more selected from these may be used in combination. Among them, the thermoplastic material is preferably a thermoplastic resin, and more preferably a polyester.
[0022] This makes it possible to more suitably control the conditions such as the glass transition point and melting point of the thermoplastic particles C2, and to improve the reliability of the molded article produced using the composite C10. This is also advantageous in reducing the production costs of the composite C10 and the molded article.
[0023] The thermoplastic particles C2 may contain components that do not have thermoplasticity in addition to the thermoplastic material as long as the thermoplastic particles C2 as a whole have thermoplasticity, such as fiber materials, colorants, flame retardants, etc.
[0024] However, the content of the thermoplastic material in the thermoplastic particles C2 is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more.
[0025] The average particle size of the thermoplastic particles C2 is preferably 1.0 μm or more and 100 μm or less, more preferably 1.0 μm or more and 60 μm or less, and even more preferably 2.0 μm or more and 40 μm or less.
[0026] This further improves the fluidity and ease of handling of the composite C10, and allows the fibers and composite C10 to be mixed more suitably when producing a molded body, thereby suppressing unintended compositional variations in the produced molded body and improving the strength, reliability, etc. of the molded body.
[0027] The composite C10 may contain thermoplastic particles C2 to which inorganic particles C3 are not attached, in other words, thermoplastic particles C2 that do not constitute composite particles C1. However, the proportion of the thermoplastic particles C2 that constitute composite particles C1 to the total thermoplastic particles C2 contained in the composite C10 is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. This allows the above-mentioned effects of the present invention to be more pronounced.
[0028] [1-1-2]Inorganic particles The composite particle C1 includes inorganic particles C3 that have been surface-treated with at least one surface treatment agent selected from the group consisting of fluorine-containing compounds and silicon-containing compounds. In other words, the inorganic particles C3 have a base particle made of an inorganic material and a coating layer made of the surface treatment agent that coats the base particle.
[0029] The average particle size of the inorganic particles C3 is preferably 1 nm or more and 300 nm or less, more preferably 5 nm or more and 100 nm or less, and even more preferably 5 nm or more and 50 nm or less.
[0030] This allows the inorganic particles C3 to be more effectively attached to the surface of the thermoplastic particles C2, and also more effectively prevents the inorganic particles from unintentionally falling off the surface of the thermoplastic particles C2 and the inorganic particles C3 from unintentionally becoming embedded inside the thermoplastic particles C2, thereby more effectively exerting the aforementioned effects.
[0031] [1-1-2-1]Mother particle The base particles of the inorganic particles C3, in other words, the base material of the inorganic particles C3 that has been surface-treated with a surface treatment agent, is made of an inorganic material.
[0032] Examples of materials constituting the base particles of the inorganic particles C3 include various metal materials, various metal compounds, various glass materials, and various carbon materials.
[0033] Examples of the metal material include elemental metals such as Fe, Al, Cu, Ag, and Ni, and alloys containing at least one of these metals.
[0034] Examples of the metal compound include metal oxides, metal nitrides, metal carbides, and metal sulfides, and more specifically, examples of the metal compound include silica, alumina, zirconia, titanium oxide, magnetite, and ferrite.
[0035] Examples of glass materials include soda glass, crystalline glass, quartz glass, lead glass, potassium glass, borosilicate glass, and non-alkali glass.
[0036] Examples of carbon materials include diamond, carbon fiber, carbon black, carbon nanotubes, carbon nanofibers, and fullerene.
[0037] Among these, silica is preferred as the material for the base particles of the inorganic particles C3. In other words, the inorganic particles C3 are preferably silica that has been surface-treated with a surface treatment agent.
[0038] This allows the surface treatment of the base particles with the surface treatment agent to be more suitably performed, and the adhesion between the base particles and the surface treatment agent can be improved. As a result, the above-mentioned effects of the present invention are more significantly exhibited. In addition, silica is a material that is less likely to adversely affect the color of the molded body produced using the composite C10. In particular, when the molded body is paper, such effects are more significantly exhibited. Furthermore, by using silica as the inorganic particles C3, the fluidity of the composite particles C1 constituting the composite C10 is improved, and the composite C10 can be more uniformly dispersed in the mixture described below. Therefore, the strength of the molded body obtained by dry molding can be further improved.
[0039] The base particles of the inorganic particles C3 may be composed mainly of the inorganic material, and may contain an organic material in addition to the inorganic material.
[0040] However, the content of the inorganic material in the base particle of the inorganic particle C3 is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 99% by mass or more.
[0041] [1-1-2-2] Surface treatment agent The inorganic particle C3 has a base particle made of an inorganic material and a coating layer made of a surface treatment agent that coats the base particle.
[0042] The surface treatment agent may be at least one selected from the group consisting of fluorine-containing compounds and silicon-containing compounds, and examples of the fluorine-containing compounds include perfluoropolyether, fluorine-modified silicone oil, etc. Examples of the silicon-containing compounds include various silicone oils such as dimethyl silicone oil, amino-modified silicone oil, epoxy-modified silicone oil, carboxy-modified silicone oil, carbinol-modified silicone oil, polyether-modified silicone oil, and alkyl-modified silicone oil.
[0043] In particular, as the surface treatment agent, it is preferably contains at least one of perfluoropolyether and dimethyl silicone oil, and more preferably contains at least perfluoropolyether.
[0044] Thereby, the surface free energy of the composite C10 can be made more suitably low, and the effects of the present invention as described above are more remarkably exhibited.
[0045] When a fluorine-containing compound and a silicon-containing compound are used as the surface treatment agent, when the amount of the fluorine-containing compound used for the surface treatment of the mother particles is XF [parts by mass] and the amount of the silicon-containing compound used for the surface treatment of the mother particles is XS [parts by mass], it preferably satisfies the relationship of 0.0 <XS / XF ≦ 4.0, more preferably satisfies the relationship of 0.1 ≦ XS / XF ≦ 3.8, and further preferably satisfies the relationship of 0.2 ≦ XS / XF ≦ 2.5.
[0046] Thereby, the surface free energy of the composite C10 can be made more suitably low, and the effects of the present invention as described above are more remarkably exhibited.
[0047] When using a plurality of types of surface treatment agents, a plurality of types of surface treatment agents may be used for a single mother particle, or the composite C10 may contain particles treated with different surface treatment agents as the inorganic particles C3.
[0048] The content of the surface treatment agent with respect to 100 parts by mass of the mother particles contained in the composite C10 is preferably 0.1 part by mass or more and 80 parts by mass or less, and more preferably 1 part by mass or more and 30 parts by mass or less. Thereby, the effects of the present invention as described above are more remarkably exhibited.
[0049] [1-1-3] Other components The composite particle C1 may have a structure in which inorganic particles C3 are attached to the surface of a thermoplastic particle C2, and may further contain other components. For example, the composite particle C1 may have inorganic particles C3 attached to the surface of a thermoplastic particle C2, and particles of an inorganic material corresponding to the base particle and not surface-treated with a surface treatment agent attached thereto.
[0050] [1-2] Other configurations The composite C10 may contain the composite particle C1 described above, and may further contain other components. For example, the composite C10 of the present invention may contain, in addition to the composite particle C1 described above, thermoplastic particles C2 to which inorganic particles C3 are not attached, or inorganic particles C3 to which thermoplastic particles C2 are not attached.
[0051] However, the content of the composite particles C1 in the composite C10 is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more. This makes the above-mentioned effects more pronounced.
[0052] [1-3] Other conditions It is preferable that the complex C10 satisfies the following conditions.
[0053] For example, when the content of thermoplastic particles C2 in composite C10 is XT [mass%] and the content of inorganic particles C3 is XI [mass%], it is preferable to satisfy the relationship of 0.001≦XI / XT≦0.25, it is more preferable to satisfy the relationship of 0.005≦XI / XT≦0.11, and it is even more preferable to satisfy the relationship of 0.006≦XI / XT≦0.05.
[0054] This makes it possible to improve the strength of a molded article produced using the composite C10.
[0055] The surface free energy of the complex C10 is 40 mJ / cm 2 Preferably, it is 37 mJ / cm or less.2 More preferably, it is 35 mJ / cm or less. 2 It is even more preferable that: This allows the above-mentioned effects of the present invention to be more pronounced.
[0056] As the surface free energy of the complex C10, a value determined by the following measurement can be used.
[0057] That is, first, a paper containing fibers such as PPC paper is prepared, and a molded body is produced using a sheet manufacturing device described later. At this time, the solid content of the composite is adjusted to be 40 mass% or more relative to the total amount of the molded body. A test piece of 10 cm x 110 cm is cut out from the molded body.
[0058] Two types of liquids with known surface tensions are dropped onto a molded body containing the composite in an environment of 23°C, and the contact angle of the liquid is measured using a dynamic absorption tester (e.g., dynamic contact angle tester 1100DAT manufactured by Fibro System AB). The measured values at eight randomly selected points are averaged to obtain the contact angle.
[0059] In the surface free energy measurement, droplets of two types of liquids with known surface tensions are dropped, and the contact angle at 0 seconds is calculated by interpolating the contact angle between 0.1 seconds and 1 second to calculate the contact angle at equilibrium excluding the influence of paper absorption, i.e., the 0 second contact angle. The surface free energy can be calculated by using the contact angle calculated as above and the known surface tensions of the two types of liquid. In the molded product, a relatively large amount of the composite is wetted and spread out due to the heating and pressing process of the manufacturing method for the molded product described later, so the surface free energy value measured for the molded product can be considered to be the surface free energy of the composite.
[0060] [2] Manufacturing method of molded body Next, the method for producing the molded article of the present invention will be described.
[0061] The method for producing a molded article of the present invention includes a depositing step of depositing a mixture containing fibers and the above-described composite of the present invention, and a heating and pressurizing step of heating and pressurizing the mixture.
[0062] This makes it possible to provide a method for producing a molded article that can produce a molded article that contains fibers and has excellent strength.
[0063] Fibers are usually the main component of the molded body produced using the molded body production method of the present invention, and are a component that greatly contributes to maintaining the shape of the molded body and also has a significant effect on the properties of the molded body, such as its strength.
[0064] The fibers may be made of any material, but it is preferable that the material be capable of maintaining the fibrous state even when heated in the heating and pressurizing step.
[0065] The fibers may be synthetic fibers composed of synthetic resins such as polypropylene, polyester, polyurethane, etc., but are preferably naturally derived fibers, i.e., biomass derived fibers, and more preferably cellulose fibers.
[0066] This makes it possible to more appropriately address environmental issues and conserve natural resources. In particular, when the fibers are cellulose fibers, the following effects can be obtained.
[0067] That is, cellulose is an abundant natural material derived from plants, and the use of cellulose as a fiber can more appropriately address environmental issues and save buried resources, etc., and is also preferable from the viewpoints of stable supply of molded products, cost reduction, etc. Furthermore, among various fibers, cellulose fibers have particularly high theoretical strength, and are advantageous from the viewpoint of further improving the strength of molded products.
[0068] Cellulosic fibers are generally composed mainly of cellulose, but may contain components other than cellulose, such as hemicellulose and lignin. The cellulose fibers used may be those that have been subjected to a treatment such as bleaching.
[0069] The fibers may also be treated with ultraviolet light, ozone, plasma, or other such treatments. This can increase the hydrophilicity of the fibers and enhance their affinity with the binding material. More specifically, these treatments can introduce functional groups such as hydroxyl groups onto the fiber surface, allowing the fibers to form hydrogen bonds more efficiently with the binding material.
[0070] The average length of the fibers is not particularly limited, but is preferably from 0.1 mm to 50 mm, more preferably from 0.2 mm to 5.0 mm, and even more preferably from 0.3 mm to 3.0 mm.
[0071] This makes it possible to improve the stability of shape, strength, etc. of the produced molded article.
[0072] The average thickness of the fibers is not particularly limited, but is preferably 0.005 mm or more and 0.5 mm or less, and more preferably 0.010 mm or more and 0.05 mm or less.
[0073] This makes it possible to improve the stability of the shape, strength, etc. of the produced molded article. In addition, it is possible to more effectively prevent the occurrence of undesired irregularities on the surface of the molded article.
[0074] The average aspect ratio of the fibers, that is, the average length to the average thickness, is not particularly limited, but is preferably 10 or more and 1,000 or less, and more preferably 15 or more and 500 or less.
[0075] This makes it possible to improve the stability of the shape, strength, etc. of the produced molded article. In addition, it is possible to more effectively prevent the occurrence of undesired irregularities on the surface of the produced molded article.
[0076] The heating temperature in the heating and pressurizing step is not particularly limited, but is preferably from 100°C to 250°C, more preferably from 120°C to 220°C, and even more preferably from 130°C to 200°C.
[0077] This allows the composite C10 to be more suitably spread on the surface of the fibers while effectively preventing undesired deterioration, denaturation, etc. of the components of the fibers and the composite C10. As a result, the strength and reliability of the produced molded article can be improved. This is also preferable from the viewpoint of energy saving.
[0078] This allows the composite C10 to more suitably wet and spread on the surface of the fibers, resulting in a molded article with superior strength.
[0079] The method for producing a molded article of the present invention can be suitably carried out, for example, by using a molded article production apparatus described below.
[0080] [3] Molded body manufacturing equipment Next, the apparatus for producing a molded article according to the present invention will be described.
[0081] Fig. 2 is a schematic side view showing the configuration of a molded body manufacturing apparatus of a preferred embodiment. Fig. 3 is a view showing the steps executed by the molded body manufacturing apparatus shown in Fig. 2 in order. For convenience of explanation, the upper side in Fig. 2 may be referred to as "upper" or "upper side", the lower side as "lower" or "lower", the left side as "left" or "upstream side", and the right side as "right" or "downstream side".
[0082] In the following description, an example of a sheet manufacturing apparatus that manufactures a sheet as a molded body will be described as an example of a molded body manufacturing apparatus.
[0083] 2, the sheet manufacturing apparatus 100, which is an apparatus for manufacturing a formed body, includes a raw material supplying section 11, a coarse crushing section 12, a defibrating section 13, a sorting section 14, a first web forming section 15, a fine dividing section 16, a mixing section 17, a refining section 18, a second web forming section 19, a sheet forming section 20, a cutting section 21, and a stocking section 22. The sheet manufacturing apparatus 100 also includes a humidifying section 231, a humidifying section 232, a humidifying section 233, and a humidifying section 234.
[0084] The operation of each unit included in the sheet manufacturing apparatus 100 is controlled by a control unit (not shown).
[0085] 3, in this embodiment, the method for manufacturing a sheet, which is a formed body, includes a raw material supplying process, a coarse crushing process, a defibrating process, a sorting process, a first web forming process, a dividing process, a mixing process, a loosening process, a second web forming process, a sheet forming process, and a cutting process. The sheet manufacturing apparatus 100 can execute these processes in order.
[0086] The configuration of each part of the sheet manufacturing apparatus 100 will be described below. The raw material supplying section 11 is a section that performs a raw material supplying step of supplying a sheet material M1 to the crushing section 12. This sheet material M1 is a sheet material that contains fibers such as cellulose fibers.
[0087] The crushing unit 12 is a section that performs a crushing step of crushing the sheet material M1 supplied from the raw material supply unit 11 in air or the like. The crushing unit 12 has a pair of crushing blades 121 and a hopper 122.
[0088] The pair of crushing blades 121 rotate in opposite directions to each other, and can crush, i.e., cut, the sheet-like material M1 between them into crushed pieces M2. The shape and size of the crushed pieces M2 are preferably suitable for defibration processing in the defibration unit 13, and are preferably small pieces with a side length of 100 mm or less, and more preferably 10 mm or more and 70 mm or less.
[0089] The hopper 122 is disposed below the pair of crushing blades 121 and has, for example, a funnel shape. This allows the hopper 122 to receive the coarsely crushed pieces M2 that have been crushed by the crushing blades 121 and dropped.
[0090] In addition, above the hopper 122, a humidifying section 231 is disposed adjacent to the pair of coarse crushing blades 121. The humidifying section 231 humidifies the coarsely crushed pieces M2 in the hopper 122. The humidifying section 231 has a filter (not shown) that contains moisture, and is configured as an evaporation-type humidifier that supplies humidified air with increased humidity to the coarsely crushed pieces M2 by passing air through the filter. By supplying the humidified air to the coarsely crushed pieces M2, it is possible to prevent the coarsely crushed pieces M2 from adhering to the hopper 122, etc. due to static electricity.
[0091] The hopper 122 is connected to the defibrating unit 13 via a pipe 241, which is a flow path. The coarse crushed pieces M2 collected in the hopper 122 pass through the pipe 241 and are transported to the defibrating unit 13.
[0092] The defibrating unit 13 is a part that performs a defibrating process in which the coarsely crushed pieces M2 are defibrated in air, i.e., in a dry manner. The defibrating process in this defibrating unit 13 can generate a defibrated material M3 from the coarsely crushed pieces M2. Here, "defibrating" refers to untangling the coarsely crushed pieces M2, which are made up of multiple fibers bound together, into individual fibers. This untangled material becomes the defibrated material M3. The shape of the defibrated material M3 is linear or band-like. The defibrated material M3 may also be present in a state where it is entangled with other pieces to form a mass, that is, in a state where it forms so-called "lumps."
[0093] In this embodiment, for example, the defibrating unit 13 is configured with an impeller mill having a rotor that rotates at high speed and a liner located on the outer periphery of the rotor. The coarse fragments M2 that flow into the defibrating unit 13 are sandwiched between the rotor and the liner and defibrated.
[0094] Furthermore, the defibrating unit 13 can generate an air flow from the crushing unit 12 to the sorting unit 14, i.e., an airflow, by the rotation of the rotor. This allows the coarsely crushed pieces M2 to be sucked into the defibrating unit 13 from the pipe 241. Furthermore, after the defibrating process, the defibrated material M3 can be sent to the sorting unit 14 via the pipe 242.
[0095] A blower 261 is installed in the middle of the pipe 242. The blower 261 is an airflow generating device that generates an airflow toward the screening section 14. This promotes the sending out of the defibrated material M3 to the screening section 14.
[0096] The sorting unit 14 is a section that performs a sorting process in which the defibrated material M3 is sorted according to the length of the fibers. In the sorting unit 14, the defibrated material M3 is sorted into a first sorted material M4-1 and a second sorted material M4-2 that is larger than the first sorted material M4-1. The first sorted material M4-1 has a size suitable for the subsequent production of the sheet S. The second sorted material M4-2 includes, for example, material that is insufficiently defibrated and material in which defibrated fibers have excessively aggregated together.
[0097] The sorting unit 14 has a drum unit 141 and a housing unit 142 that houses the drum unit 141.
[0098] The drum part 141 is a sieve composed of a cylindrical mesh body and rotates around its central axis. The defibrated material M3 flows into this drum part 141. Then, as the drum part 141 rotates, the defibrated material M3 smaller than the mesh opening is sorted as the first sorted material M4-1, and the defibrated material M3 larger than the mesh opening is sorted as the second sorted material M4-2. The first sorted item M4-1 falls from the drum portion 141.
[0099] Meanwhile, the second sorted material M4-2 is sent to pipe 243, which is a flow path connected to the drum unit 141. Pipe 243 is connected to pipe 241 on the opposite side to the drum unit 141, i.e., the upstream side. The second sorted material M4-2 that passes through this pipe 243 merges with the coarsely crushed pieces M2 in pipe 241 and flows into the defibrating unit 13 together with the coarsely crushed pieces M2. As a result, the second sorted material M4-2 is returned to the defibrating unit 13 and is defibrated together with the coarsely crushed pieces M2.
[0100] The first selected material M4-1 from the drum unit 141 falls while being dispersed in the air, and heads toward the first web forming unit 15, which is a separation unit located below the drum unit 141. The first web forming unit 15 is a unit that performs a first web forming step of forming the first web M5 from the first selected material M4-1. The first web forming unit 15 has a mesh belt 151, which is a separation belt, three tension rollers 152, and a suction unit 153.
[0101] The mesh belt 151 is an endless belt on which the first sorted material M4-1 is accumulated. The mesh belt 151 is wound around three tension rollers 152. As the tension rollers 152 rotate, the first sorted material M4-1 on the mesh belt 151 is transported downstream.
[0102] The size of the first sorted material M4-1 is equal to or larger than the mesh size of the mesh belt 151. This restricts the passage of the first sorted material M4-1 through the mesh belt 151, and therefore the first sorted material M4-1 can be piled up on the mesh belt 151. Furthermore, the first sorted material M4-1 is transported downstream together with the mesh belt 151 while being piled up on the mesh belt 151, and is thus formed as a layered first web M5.
[0103] Furthermore, the first sorted material M4-1 may contain, for example, dust and dirt. For example, dust and dirt may be mixed in together with the sheet material M1 when the sheet material M1 is supplied from the raw material supply section 11 to the crushing section 12. The dust and dirt are smaller than the mesh size of the mesh belt 151. As a result, the dust and dirt pass through the mesh belt 151 and fall further downward.
[0104] The suction section 153 can suck air from below the mesh belt 151. This makes it possible to suck in dust and dirt that has passed through the mesh belt 151 together with the air.
[0105] In addition, the suction unit 153 is connected to the collection unit 27 via a pipe 244 which is a flow path. The dust and dirt sucked by the suction unit 153 is collected in the collection unit 27.
[0106] A pipe 245, which is a flow path, is further connected to the collection unit 27. A blower 262 is installed midway through the pipe 245. By operating the blower 262, a suction force can be generated in the suction unit 153. This promotes the formation of the first web M5 on the mesh belt 151. Dust and dirt are removed from this first web M5. By operating the blower 262, the dust and dirt pass through the pipe 244 and reach the collection unit 27.
[0107] The housing part 142 is connected to the humidifier part 232. The humidifier part 232 is configured as an evaporative humidifier similar to the humidifier part 231. This allows humidified air to be supplied into the housing part 142. The first sorted item M4-1 can be humidified by this humidified air, and therefore, the first sorted item M4-1 can be prevented from adhering to the inner wall of the housing part 142 due to electrostatic force.
[0108] A humidifying section 235 is disposed downstream of the sorting section 14. The humidifying section 235 is configured with an ultrasonic humidifier that sprays water. This allows moisture to be supplied to the first web M5, and thus the moisture content of the first web M5 is adjusted. This adjustment makes it possible to suppress adhesion of the first web M5 to the mesh belt 151 due to electrostatic force. As a result, the first web M5 is easily peeled off from the mesh belt 151 at the position where the mesh belt 151 is folded back by the tension roller 152.
[0109] The segmentation unit 16 is disposed downstream of the humidification unit 235. The segmentation unit 16 is a section that performs a segmentation step of segmenting the first web M5 peeled off from the mesh belt 151. The segmentation unit 16 has a rotatably supported propeller 161 and a housing portion 162 that houses the propeller 161. The first web M5 is wound around the rotating propeller 161, so that the first web M5 can be segmented. The segmented first web M5 becomes segmented bodies M6. The segmented bodies M6 move down inside the housing portion 162.
[0110] The housing part 162 is connected to the humidifier part 233. The humidifier part 233 is configured with an evaporation type humidifier similar to the humidifier part 231. This allows humidified air to be supplied into the housing part 162. This humidified air can also prevent the fragmented bodies M6 from adhering to the propeller 161 and the inner wall of the housing part 162 due to electrostatic force.
[0111] A mixing section 17 is disposed downstream of the subdivision section 16. The mixing section 17 is a section in which a mixing step is performed in which the subdivision bodies M6 are mixed with the composite C10 of the present invention described above. The mixing section 17 has a composite supply section 171, a pipe 172 which is a flow path, and a blower 173.
[0112] The pipe 172 connects the housing portion 162 of the subdivision section 16 and the housing portion 182 of the disintegration section 18, and is a flow path through which the mixture M7 of the subdivision bodies M6 and the complexes C10 passes.
[0113] A composite material supplying section 171 is connected to the middle of the pipe 172. The composite material supplying section 171 has a screw feeder 174. The screw feeder 174 is driven to rotate, thereby supplying the composite material C10 to the pipe 172. The composite material C10 supplied to the pipe 172 is mixed with the fragmented bodies M6 to become the mixture M7.
[0114] In addition, the composite supply unit 171 may contain, together with the composite C10, for example, a colorant for coloring the fibers, an aggregation inhibitor for inhibiting aggregation of the fibers or aggregation of the composite C10, and a flame retardant for making the fibers, etc. less flammable.
[0115] Further, a blower 173 is provided in the middle of the pipe 172, downstream of the complex supply unit 171. The blower 173 can generate an airflow toward the disintegrating unit 18. This airflow can agitate the fragmented bodies M6 and the complex C10 in the pipe 172. This allows the mixture M7 to flow into the disintegrating unit 18 in a state in which the fragmented bodies M6 and the complex C10 are uniformly dispersed. Furthermore, the fragmented bodies M6 in the mixture M7 are disintegrated in the process of passing through the pipe 172, becoming finer fibrous.
[0116] The disentanglement unit 18 is a unit that performs a disentanglement step of disentangling entangled fibers in the mixture M7. The disentanglement unit 18 has a drum unit 181 and a housing unit 182 that houses the drum unit 181.
[0117] The drum section 181 is a sieve that is composed of a cylindrical mesh body and rotates around its central axis. The mixture M7 flows into the drum section 181. As the drum section 181 rotates, fibers and the like of the mixture M7 that are smaller than the mesh openings can pass through the drum section 181. At that time, the mixture M7 is loosened.
[0118] Furthermore, the mixture M7 loosened by the drum section 181 falls while being dispersed in the air, and heads toward the second web forming section 19 located below the drum section 181. The second web forming section 19 is a section where a second web forming step is performed in which a second web M8 is formed from the mixture M7. The second web forming step in this embodiment is a deposition step in which a mixture containing fibers and a composite C10 is deposited. The second web forming section 19 has a mesh belt 191 which is a separation belt, a tension roller 192, and a suction section 193.
[0119] The mesh belt 191 is an endless belt on which the mixture M7 is accumulated. The mesh belt 191 is wound around four tension rollers 192. The mixture M7 on the mesh belt 191 is transported downstream by the rotation of the tension rollers 192.
[0120] Moreover, most of the mixture M7 on the mesh belt 191 has a size equal to or larger than the mesh openings of the mesh belt 191. This prevents the mixture M7 from passing through the mesh belt 191, and therefore the mixture M7 can be accumulated on the mesh belt 191. Moreover, the mixture M7 is transported downstream together with the mesh belt 191 while being accumulated on the mesh belt 191, and is thus formed as a layered second web M8.
[0121] The suction unit 193 can suck air from below the mesh belt 191. This allows the mixture M7 to be sucked onto the mesh belt 191, thereby facilitating the accumulation of the mixture M7 on the mesh belt 191.
[0122] A pipe 246, which is a flow path, is connected to the suction unit 193. A blower 263 is provided midway through the pipe 246. By operating the blower 263, the suction unit 193 can generate a suction force.
[0123] The housing part 182 is connected to the humidifier part 234. The humidifier part 234 is configured as an evaporation type humidifier similar to the humidifier part 231. This allows humidified air to be supplied into the housing part 182. The inside of the housing part 182 can be humidified by this humidified air, and therefore, it is also possible to prevent the mixture M7 from adhering to the inner wall of the housing part 182 due to electrostatic force.
[0124] A humidifying section 236 is disposed downstream of the refining section 18. The humidifying section 236 is configured with an ultrasonic humidifier similar to the humidifying section 235. This allows moisture to be supplied to the second web M8, and thus the moisture content of the second web M8 is adjusted. This adjustment makes it possible to suppress adhesion of the second web M8 to the mesh belt 191 due to electrostatic force. This allows the second web M8 to be easily peeled off from the mesh belt 191 at the position where the mesh belt 191 is folded back by the tension roller 192.
[0125] A sheet forming unit 20 is disposed downstream of the second web forming unit 19. The sheet forming unit 20 is a section that performs a sheet forming process, which is a heating and pressurizing process for forming a sheet S from the second web M8. The sheet forming unit 20 has a pressurizing unit 201 and a heating unit 202.
[0126] The pressurizing unit 201 has a pair of calender rollers 203, and can pressurize the second web M8 between them without heating it. This increases the density of the second web M8. Then, the second web M8 is transported toward the heating unit 202. One of the pair of calender rollers 203 is a driven roller driven by the operation of a motor (not shown), and the other is a driven roller.
[0127] The heating section 202 has a pair of heating rollers 204, and can apply pressure to the second web M8 while heating it therebetween. This heating and pressurization causes the composite C10 to melt in the second web M8, and the fibers are bonded to each other via the molten composite C10. This forms a sheet S as a molded body. Then, this sheet S is transported toward the cutting section 21. Note that one of the pair of heating rollers 204 is a driven roller driven by the operation of a motor (not shown), and the other is a driven roller.
[0128] The cutting unit 21 is disposed downstream of the sheet forming unit 20. The cutting unit 21 is a portion that performs a cutting step of cutting the sheet S. The cutting unit 21 has a first cutter 211 and a second cutter 212.
[0129] The first cutter 211 cuts the sheet S in a direction intersecting the conveying direction of the sheet S.
[0130] The second cutter 212 is located downstream of the first cutter 211 and cuts the sheet S in a direction parallel to the conveying direction of the sheet S.
[0131] The sheet S is obtained as a compact having a desired size by cutting with the first cutter 211 and the second cutter 212. The sheet S is then transported further downstream and accumulated in the stock section 22.
[0132] [4] Molded body Next, the molded article of the present invention will be described.
[0133] The molded body of the present invention includes fibers, inorganic particles that have been surface-treated with at least one surface treatment agent selected from the group consisting of fluorine-containing compounds and silicon-containing compounds, and a thermoplastic material that bonds the fibers and the inorganic particles. This makes it possible to provide a molded article that contains fibers and has excellent strength.
[0134] The thermoplastic material and inorganic particles contained in the molded article of the present invention preferably satisfy the same conditions as those explained in the above [1-1-1] and [1-1-2], respectively.
[0135] The shape of the molded product of the present invention is not particularly limited and may be any shape, such as a sheet, a block, a sphere, or a three-dimensional shape, but the molded product of the present invention is preferably in the form of a sheet. Note that the sheet shape referred to here means a thickness of 30 μm to 30 mm and a density of 0.05 g / cm. 3 More than 1.5g / cm 3This refers to a molded body molded as follows:
[0136] This allows the molded article to be suitably used as, for example, a recording medium, etc. Furthermore, by using the above-mentioned device, the molded article can be produced more efficiently.
[0137] When the molded article of the present invention is a sheet-shaped recording medium, its thickness is preferably 30 μm or more and 3 mm or less.
[0138] This allows the molded article to be more suitably used as a recording medium. Also, by using the above-mentioned apparatus, the molded article can be produced more efficiently.
[0139] When the molded article of the present invention is a sheet-shaped recording medium, its density is 0.6 g / cm 3 More than 0.9g / cm 3 It is preferable that: This allows the molded article to be more suitably used as a recording medium. This allows the molded article to be more suitably used as a liquid absorbent.
[0140] The molded article of the present invention may be at least partially manufactured by applying the above-mentioned manufacturing method of the molded article of the present invention, and may further include other parts. Also, the molded article of the present invention may be subjected to post-treatment after the steps described in the manufacturing method of the molded article of the present invention.
[0141] The uses of the molded article of the present invention are not particularly limited, and examples thereof include recording media, liquid absorbents, cushioning materials, and sound absorbing materials.
[0142] Furthermore, the molded article of the present invention can be suitably produced, for example, by using the above-described composite of the present invention and the method for producing a molded article of the present invention. However, as long as it has the above-described configuration, it may be produced using any material and method.
[0143] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to these.
[0144] For example, each component of the sheet manufacturing apparatus may be replaced with any component that can exert a similar function. Also, any component may be added.
[0145] Furthermore, the molded article of the present invention is not limited to one produced using the above-mentioned apparatus, and may be one produced using any apparatus. EXAMPLES
[0146] Next, specific examples of the present invention will be described. [5] Preparation of the complex Example 1 First, polyester resin "Vylon 220" manufactured by Toyobo Co., Ltd. was prepared, which was then coarsely crushed and then crushed into particles with a diameter of 1 mm or less using a hammer mill (manufactured by Dalton Co., Ltd., product name "Labo Mill LM-5"). The crushed particles were then crushed using a jet mill (manufactured by Japan Pneumatic Co., Ltd., product name "PJM-80SP") to obtain particles with a maximum particle size of 40 μm or less. These particles were classified using an air classifier (manufactured by Japan Pneumatic Co., Ltd., product name "MDS-3") to obtain thermoplastic particles with an average particle size of 10.0 μm.
[0147] On the other hand, fumed silica (manufactured by Nippon Aerosil Co., Ltd., product name "AEROSIL R972" (average particle size 16 nm)) was added to a surface treatment liquid consisting of 50 parts by mass of dimethyl silicone oil as a surface treatment agent and 300 parts by mass of ethyl acetate, stirred and mixed, and then filtered, dried, and pulverized in a pin mill to obtain inorganic particles in which the fumed silica was surface-treated with dimethyl silicone oil.
[0148] 100 parts by mass of the thermoplastic particles obtained as described above and 2 parts by mass of inorganic particles were added to a blender (manufactured by Waring Corporation, product name "Waring Blender Type 7012") and mixed at a rotation speed of 15,600 rpm for 60 seconds to obtain a composite containing composite particles in which the inorganic particles were adhered to the surfaces of the thermoplastic particles.
[0149] Example 2 A composite was prepared in the same manner as in Example 1, except that the surface treatment of the fumed silica was carried out in a surface treatment liquid consisting of 45 parts by mass of dimethyl silicone oil, 5 parts by mass of perfluoropolyether, and 300 parts by mass of ethyl acetate.
[0150] Example 3 A composite was prepared in the same manner as in Example 1, except that the surface treatment of the fumed silica was carried out in a surface treatment liquid consisting of 35 parts by mass of dimethyl silicone oil, 15 parts by mass of perfluoropolyether, and 300 parts by mass of ethyl acetate.
[0151] Example 4 A composite was prepared in the same manner as in Example 1, except that the surface treatment of the fumed silica was carried out in a surface treatment liquid consisting of 25 parts by mass of dimethyl silicone oil, 25 parts by mass of perfluoropolyether, and 300 parts by mass of ethyl acetate.
[0152] Example 5 A composite was prepared in the same manner as in Example 1, except that the surface treatment of the fumed silica was carried out in a surface treatment liquid consisting of 15 parts by mass of dimethyl silicone oil, 35 parts by mass of perfluoropolyether, and 300 parts by mass of ethyl acetate.
[0153] Example 6 A composite was prepared in the same manner as in Example 1, except that the surface treatment of the fumed silica was carried out in a surface treatment liquid consisting of 5 parts by mass of dimethyl silicone oil, 45 parts by mass of perfluoropolyether, and 300 parts by mass of ethyl acetate.
[0154] Example 7 A composite was prepared in the same manner as in Example 1, except that the surface treatment of the fumed silica was carried out in a surface treatment liquid consisting of 50 parts by mass of perfluoropolyether and 300 parts by mass of ethyl acetate.
[0155] The fact that the inorganic particles used in the manufacture of the composites of each of the above examples were in a state in which the surfaces of the base particles were surface-treated with a surface treatment agent was confirmed by high performance liquid chromatography as follows. That is, first, the dried inorganic particles were immersed in a mixed liquid in which hexane and diethyl ether were mixed at a mass ratio of 1:1 to elute the surface treatment agent. Thereafter, the eluted mixed liquid was distilled under a nitrogen atmosphere, and the residue was dissolved in tetrahydrofuran to prepare a sample for high performance liquid chromatography. The solution was supplied to an analytical column at a flow rate of 0.5 mL / min, and the surface treatment agent was detected by a differential refractive index (RI) detector.
[0156] Comparative Example 1 100 parts by mass of thermoplastic particles having an average particle size of 10 μm prepared in the same manner as described in Example 1 and 1 part by mass of non-surface-treated fumed silica (manufactured by Nippon Aerosil Co., Ltd., product name "AEROSIL R972" (average particle size 16 nm)) were put into a blender (manufactured by Waring Co., Ltd., product name "Waring Blender 7012 type") and mixed at a rotation speed of 15,600 rpm for 60 seconds to obtain a composite. That is, in this comparative example, the surface of the fumed silica, which is an inorganic particle, was not surface-treated with a surface treatment material.
[0157] The configurations of the composites of each of the above-mentioned Examples and Comparative Example 1 are summarized in Table 1. In addition, in Table 1, a composition consisting of only thermoplastic particles having an average particle size of 10 μm prepared in the same manner as described in the above-mentioned Example 1 is shown as Comparative Example 2. In addition, the value of XS / XF when the amount of the fluorine-containing compound used in the surface treatment of the inorganic particle base particle is XF [parts by mass], the amount of the silicon-containing compound used in the surface treatment of the inorganic particle base particle is XS [parts by mass], the content of the thermoplastic particles is XT [% by mass], and the content of the inorganic particles is XI [% by mass]. In each of the above-mentioned Examples, the proportion of the thermoplastic particles constituting the composite particles to the total thermoplastic particles contained in the composite was 90% by mass or more, and the proportion of the inorganic particles constituting the composite particles to the total inorganic particles contained in the composite was 90% by mass or more.
[0158] [Table 1]
[0159] [6] Manufacturing of molded bodies Using the composites of each of the Examples and Comparative Example 1, sheets were produced as molded articles in the following manner.
[0160] First, a sheet manufacturing apparatus as shown in FIG. 2 was prepared, and PPC paper (Toppan Forms Multicut Paper White) was prepared as a sheet material as a fiber source.
[0161] Next, the sheet-like material was fed to the raw material feed section of the sheet manufacturing apparatus, and the sheet manufacturing apparatus was operated to carry out the processes of coarse crushing, defibrating, sorting, first web forming, dividing, mixing, loosening, second web forming, sheet forming, and cutting, to produce an A4 size sheet as a formed body. The thickness of the obtained sheet was 130 μm.
[0162] At this time, the composition was adjusted so that the sheet as the final molded product contained 20 parts by mass of the fiber and 5 parts by mass of the composite as the raw material. The heating temperature when heating and pressing in the heating section was 180° C., the pressure when heating and pressing in the heating section was 25 MPa, and the heating and pressing time when heating and pressing in the heating section was 1 second.
[0163] In addition, in Comparative Example 2, a sheet was produced in the same manner as above, except that thermoplastic particles were used instead of the composite.
[0164] [7] Evaluation [7-1] Surface free energy For each of the composites of the above-mentioned Examples and Comparative Example 1, the surface free energy was determined as follows.
[0165] That is, first, PPC paper (Toppan Forms Multicut Paper White) was used as a raw material, and a molded body containing the composite was produced using a sheet manufacturing device. The composite contained in the molded body was adjusted to 40 mass %. A test piece of 10 cm x 110 cm was cut out from the molded body.
[0166] Water and ethylene glycol (manufactured by Wako Pure Chemical Industries, Ltd.), which have known surface tensions, were dropped onto a molded body containing the composite in an environment of 23°C, and the contact angles of the water and ethylene glycol were measured using a dynamic absorption tester (manufactured by Fibro System AB, dynamic contact angle tester 1100DAT). The measured values at eight randomly selected points were averaged to obtain the contact angle.
[0167] In the surface free energy measurement, droplets of water and ethylene glycol were dropped, and the contact angle at 0 seconds was calculated by interpolating the contact angle between 0.1 and 1 seconds to obtain the contact angle at 0 seconds, which is the equilibrium contact angle excluding the influence of paper absorption, i.e., the 0 second contact angle. The surface free energy was calculated using the contact angle obtained as above and the surface tension of water and ethylene glycol.
[0168] For Comparative Example 2, the surface free energy was determined in the same manner as above, except that thermoplastic particles were used instead of the composite.
[0169] [7-2] Blocking A portion of each of the composites of the above-mentioned Examples and Comparative Example 1, and the thermoplastic particles of Comparative Example 2 was placed in a glass container and left to stand at 23°C for 24 hours. The state of the composites was then visually observed to confirm whether or not the particles had agglomerated, i.e., whether or not blocking had occurred.
[0170] [7-3] Tensile strength The sheets of each Example and Comparative Example obtained in [6] above were subjected to a tensile test in accordance with JIS P 8113. More specifically, a test piece having a total length of 180 mm was cut out from each sheet, and then a tensile test was carried out on the test piece at an extension speed of 20 mm / min. The breaking stress (MPa) of the test piece was calculated as the tensile strength from the maximum load until the test piece broke, and was evaluated according to the following criteria. The tensile test was carried out in accordance with JIS P 8111 at a room temperature of 23°C and a humidity of 50%.
[0171] A: Tensile strength is over 24 MPa. B: Tensile strength is more than 20 MPa and 24 MPa or less. C: Tensile strength is 20 MPa or less. These results are summarized in Table 2.
[0172] [Table 2]
[0173] As is clear from Table 2, excellent results were obtained in the present invention. In contrast, satisfactory results were not obtained in the comparative examples.
[0174] In addition, composites were produced in the same manner as in each of the above Examples, except that the average particle size of the thermoplastic particles was variously changed within the range of 1.0 μm or more and 100 μm or less, the average particle size of the inorganic particles was variously changed within the range of 1 nm or more and 300 nm or less, the average particle size of the composite particles was variously changed within the range of 1.0 μm or more and 100 μm or less, and the value of XI / XT, where XT [mass%] is the content of the thermoplastic particles and XI [mass%] is the content of the inorganic particles, was variously changed within the range of 0.001 or more and 0.25 or less. These composites were evaluated in the same manner as above, and the same results as above were obtained. [Explanation of symbols]
[0175] 100...sheet manufacturing apparatus, 11...raw material supply section, 12...crushing section, 121...crushing blade, 122...hopper, 13...defibrating section, 14...screening section, 141...drum section, 142...housing section, 15...first web forming section, 151...mesh belt, 152...tension roller, 153...suction section, 16...fragmenting section, 161...propeller, 162...housing section, 17...mixing section, 171...composite supply section, 172...pipe, 173...blower, 174...screw feeder, 18...loosening section, 181...drum section, 182...housing section, 19...second web forming section, 191...mesh belt, 192...tension roller, 193...suction section, 20...sheet forming section, 201...pressure section, 202...heating section, 20 3...calender roller, 204...heating roller, 21...cutting section, 211...first cutter, 212...second cutter, 22...stock section, 231...humidifying section, 232...humidifying section, 233...humidifying section, 234...humidifying section, 235...humidifying section, 236...humidifying section, 241...tube, 242...tube, 243...tube, 244...tube, 245...tube, 246...tube, 261 ...blower, 262...blower, 263...blower, 27...recovery section, C10...composite, C1...composite particles, C2...thermoplastic particles, C3...inorganic particles, M1...sheet-like material, M2...coarsely crushed pieces, M3...defibrated material, M4-1...first sorted material, M4-2...second sorted material, M5...first web, M6...fragmented body, M7...mixture, M8...second web, S...sheet
Claims
1. Thermoplastic particles made of a thermoplastic resin; and inorganic particles surface-treated with a surface treatment agent containing a fluorine-containing compound, The fiber binder comprises composite particles in which the inorganic particles are attached to the surfaces of the thermoplastic particles, and the composite particles have a surface free energy of 40 mJ per square centimeter or less.
2. The fiber binder according to claim 1 , wherein the surface treatment agent contains a perfluoropolyether.
3. 3. The fiber binder according to claim 1, wherein the surface free energy is 37 mJ or less per square centimeter.
4. 4. The fiber binder according to claim 3, having a surface free energy of 35 mJ or less per square centimeter.
5. A depositing step of depositing a mixture containing fibers and the fiber binder according to any one of claims 1 to 4; and a heating and pressurizing step of heating and pressurizing the mixture.
Citation Information
Patent Citations
Developer for electrophotography
JP1985093455A
Hydrophobic silica powder and its manufacturing method
JP2002256170A
Flame-retardant fiber-reinforced polymer composition
JP2003226816A
Binder for inorganic fiber non-woven fabric
JP2011226045A
Sheet production device and sheet production method
JP2016145427A